(untitled) (Proceedings of International Educators Conference, 2024)
Eye injury severity assessment is carried out in accordance with the Criminal Code of the Republic of Uzbekistan [2]. Criteria for determining the severity of harm to health are specified in paragraph 9 of the decree No.153 issued by the Ministry of Health of the Republic of Uzbekistan on June 1, 2012, titled "Percentage of permanent loss of general work capacity due to various types of injuries, poisoning external factors, and other external causes" [3]. In daily forensic medical practice, three criteria are mainly considered: "the danger to life at the time of injury", "the duration of recovery from health impairment" and "the percentage of permanent or temporary loss of general work capacity" as indicated in the table based on the percentages of loss of work capacity due to injuries and external factors. The duration of the health impairment cannot objectively reflect the severity of harm to health since it is subjective [1, 6].